Cutaneous Acquired Toxoplasmosis in a Child: A Case Report and Review of the Literature. (April 2015) - Rand, Andrew J.; Buck, Andrew B.; Love, Porcia B.; Prose, Neil S.; Selim, M. Angelica
Abstract : Abstract: Cutaneous toxoplasmosis is a rare and diagnostically challenging entity. Today, the acquired form occurs predominantly in immunocompromised patients with human immunodeficiency virus or after hematopoietic stem cell transplantation. We report a case of cutaneous toxoplasmosis in a 6-year-old girl after allogeneic stem cell transplantation for immune-mediated encephalopathy, first manifesting at 16 months of age. In the post-transplant setting, she developed a rash consisting of approximately 8 scattered 3–4-mm round, erythematous macules and papules on her back, abdomen, and right shoulder. Sections from a biopsy of a lesion on the back revealed numerous spherules tightly packed within small cystic structures in the epidermis. The diagnosis of cutaneous toxoplasmosis was confirmed by an immunohistochemical stain for Toxoplasma gondii and polymerase chain reaction on the peripheral blood for the T. gondii genome. This case should raise awareness that acquired toxoplasmosis with cutaneous involvement can occur in the pediatric population, particularly in immunocompromised patients after stem cell transplantation. Early diagnosis and treatment of this life-threatening opportunistic infection may improve patient outcomes.